Analisis Keberlanjutan Penggunaan Alat Tangkap Pancing Ulur Dan Jaring Udang Di Desa Blitok Kabupaten Situbondo - Handayani, Creani; Utami, Pratita Budi; Emeliya, Alfiyah; Syaifurrijal, Moh. (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
Blitok Village at Situbondo Regency is a village that borders directly on The North of the Java Sea. Fishermen use handlines and shrimp nets because of a low budget and ease of operation. These fishing gear are considered environmentally friendly. At that time, data and information regarding these fishing are rather specific. Therefore, this research aims to dig into the use of these fishing gear from ecological, economic, and social aspects. Ecological aspects will be using CPUE Analysis. We discuss economics with the use of Financial Analysis. The Perception Analysis is used for the social part. This research was carried out by census because the population observed was 16 fishermen. The observations showed CPUE values ​​were not good enough. It was also confirmed by financial analysis results. As a project, this business activity is not feasible. However, until now, this activity is still carried out by fishermen. Even though, 50% of fishermen admit that their condition is still less than prosperous. 75% of fishermen agree that this activity is Just Enough to support family income.